Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (Research ICT Africa, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Gender Roles, Relationships and Social Equity in Post-Harvest Management in Mozambique - FANRPAN (ood, Agriculture and Natural Resources Policy Analysis Network, 2018)
Key Recommendations: 1. Gender and other general policies in the agricultural sector should be revised to reflect clear priorities for lowering post-harvest losses (PHL). 2. Crop scientists should be trained and crop-specific PHM research infrastructure should be developed so that PHM can be included as a research component for all crops. 3. Academic and research units should be located in the field, close to the farmers, so that researchers and/or university students are closer to the beneficiaries. 4. PHM programs, projects, and activities must include information and technology development and dissemination relevant to the end-users, including women, children, the youth, and poorer farmers. 5. PHL should be reduced by increasing access to carts/wheelbarrows and their respective repair kits and to draught animals, repairing critical sections of rural roads, and increasing farmers’ access to bags/sacks that are not infested and in good condition. 6. Reduce PHL along the value chain from farm to plate by extending innovations to some of the socially perceived “female-roles” of PHM. 7. Development and dissemination of PHM innovations must also be part of policies, strategies, and practices to promote a better workload distribution by increasing male participation in labourdemanding PHM activities culturally assigned to women. 8. Since women in polygamous marriages and single mothers are easier to work with when it comes to promoting investment in PHM improvements due to their decision-making power in the households, they should be given priority in work plans. 9. Prioritize female farmers in PHM capacity-building initiatives, because they are the ones who deal with most of the PHM activities. 10. Local tools manufacturers should benefit from incentives to lower the cost for the development of manufacturing, processing, and packaging equipment to make them accessible to women and the poor.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; gender / género

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Gender in Political Economy Analysis - Browne, Evie (GSDRC, University of Birmingham, 2014)
This report provides a brief examination of how and where gender analysis is incorporated into Political Economy Analysis (PEA). An initial review of the literature indicates that gender is not systematically included in PEA. This was also conveyed by a number of experts consulted for this report, who stated that few if any PEAs to their knowledge had included a gender analysis, with the issue usually treated only in passing. The report nevertheless highlights the existing examples of gender-oriented analytical questions used in common PEA tools. It also identifies areas of overlap between gender and political economy analysis.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); gender / género

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Gender and poverty in Mozambique - Tvedten, Inge (CMI, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found